Coming to GRIPs With NETs Discourse: Implications of Discursive Structures for Emerging Governance of Negative Emissions Technologies in the UK - Boettcher, Miranda (Frontiers in Climate, 2020)
As the international community rallies around Net-Zero emissions targets, there is increasing interest in the development of governance for Negative Emissions Technologies (NETs), a range of proposed approaches which involve removing greenhouse gases from the atmosphere. It has been pointed out that the governance development process should include ‘opening up’ the discussion NETs governance, moving the debate beyond the bounds of technocratic, neoliberal discourse and thereby paving the way for more responsible, inclusive governance of technologies. The implication is that there is a constitutive and qualitative link between discourse and governance – that governance development is shaped by discourse. However, so far there has been limited work done to link empirical mapping of the discursive structures in different spheres of the NETs debate to theoretically-informed anticipation of how these structures may influence governance development. This paper presents a sociology-of-knowledge (SKAD) discourse analysis of a series of interviews with UK representatives from the industry/policy interface about what they consider to be appropriate governance instruments for NETs. Linking discursive structures to governance development using the concept of governmentality, the paper critically discusses how a set of political, economic and ethical discursive structures currently underpinning the industry and policy spheres of the UK NETs debate may be shaping governance development. The paper shows what types of discourse/knowledge and social actors are being privileged/excluded within the structure of the UK NETs debate, and highlights ways in which discursive mapping can play a key emancipatory role in ‘opening’ up governance development processes.